2014
DOI: 10.1161/atvbaha.113.302655
|View full text |Cite
|
Sign up to set email alerts
|

Protein S Is a Cofactor for Platelet and Endothelial Tissue Factor Pathway Inhibitor-α but Not for Cell Surface–Associated Tissue Factor Pathway Inhibitor

Abstract: Objective Tissue factor pathway inhibitor (TFPI) is produced in 2 isoforms: TFPIα, a soluble protein in plasma, platelets, and endothelial cells, and TFPIβ, a glycosylphosphatidylinositol-anchored protein on endothelium. Protein S (PS) functions as a cofactor for TFPIα, enhancing the inhibition of factor Xa. However, PS does not alter the inhibition of prothrombinase by TFPIα, and PS interactions with TFPIβ are undescribed. Thus, the physiological role and scope of the PS–TFPI system remain unclear. Approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 49 publications
(60 reference statements)
2
52
0
Order By: Relevance
“…In contrast, protein S does not enhance the activity of membrane-associated TFPI (TFPIb). 35 Because membrane-bound TFPI does not have a Kunitz domain 3, their study confirmed the importance of this domain for the protein S enhancement. Wood et al also created a TFPIb variant containing a Kunitz domain 3 but, for reasons that are not clear, protein S was unable to enhance this TFPI variant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, protein S does not enhance the activity of membrane-associated TFPI (TFPIb). 35 Because membrane-bound TFPI does not have a Kunitz domain 3, their study confirmed the importance of this domain for the protein S enhancement. Wood et al also created a TFPIb variant containing a Kunitz domain 3 but, for reasons that are not clear, protein S was unable to enhance this TFPI variant.…”
Section: Discussionmentioning
confidence: 87%
“…It has previously been hypothesized that protein S, through its high affinity for negatively charged phospholipids, brings TFPI in close proximity to FXa on an activated membrane and thereby increases the TFPI/FXa association rate. [15][16][17]35 We propose that protein S and TFPI can associate in plasma through a direct interaction between the protein S SHBG-like domain and the TFPI Kunitz 3 domain, particularly with Glu226. Upon initiation of coagulation on phospholipid surfaces, protein S brings TFPI Kunitz domain 2 into proximity of the active site of the protease domain of FXa, thereby decreasing the concentration of TFPI needed for efficient inhibition of FXa ( Figure 6).…”
Section: Tfpi Cofactor Function Of Protein S 3985mentioning
confidence: 95%
See 1 more Smart Citation
“…6 Thus, it appears that PS enhances FXa inhibition primarily by localizing TFPIa to the membrane surface, a notion supported by experiments demonstrating that PS has cofactor activity toward the soluble TFPI variant protein K1K2K3 8,115 but has no cofactor activity toward the same variant protein when it is attached to the cell surface with a GPI anchor. 115 In addition, PS does not enhance inhibition of FXa by cell surface-associated TFPI on primary endothelial cells or endothelial cell lines. 115 Because optimal inhibition of FXa by TFPIa requires both the K3 domain and the basic C terminus 8,64,107-110 (regions which are not present in TFPIb), one might hypothesize that TFPIb would be a relatively poor inhibitor of FXa.…”
Section: Inhibition Of Fxa By Tfpia and Tfpibmentioning
confidence: 96%
“…115 In addition, PS does not enhance inhibition of FXa by cell surface-associated TFPI on primary endothelial cells or endothelial cell lines. 115 Because optimal inhibition of FXa by TFPIa requires both the K3 domain and the basic C terminus 8,64,107-110 (regions which are not present in TFPIb), one might hypothesize that TFPIb would be a relatively poor inhibitor of FXa. However, this is not the case.…”
Section: Inhibition Of Fxa By Tfpia and Tfpibmentioning
confidence: 96%